1995
DOI: 10.2134/agronj1995.00021962008700010009x
|View full text |Cite
|
Sign up to set email alerts
|

Barley, Canola, and Weed Growth with Decreasing Tillage in a Cold, Semiarid Climate

Abstract: Conventional tillage systems are reported to cause soil degradation, yet appropriate conservation tillage practices have not been developed for cold regions of the northern Canadian Prairies. Effects of conventional, reduced, and zero tillage systems (CT, RT, and ZT) on the growth of dryland spring barley (Hordeum vulgare L.), canola (Brassica campestris L.), and weeds were studied on a clay soil (Natriboralf) near Rycroft in northern Alberta. Each crop‐tillage combination was fixed in space from 1989 through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…Conversely to crop biomass, the main tillage effects in both years were lower weed biomass production under CT in both varieties, and a lower production in 1999 than in 2000 (Figure 2). These results are in agreement with Arshad et al (1995) who found a higher weed mass in NT than in CT. In no-tillage systems, the weed seeds remain in the upper layer and ) under two tillage systems (CT: conventional tillage, NT: No-tillage).…”
Section: Soil Tillagesupporting
confidence: 93%
See 2 more Smart Citations
“…Conversely to crop biomass, the main tillage effects in both years were lower weed biomass production under CT in both varieties, and a lower production in 1999 than in 2000 (Figure 2). These results are in agreement with Arshad et al (1995) who found a higher weed mass in NT than in CT. In no-tillage systems, the weed seeds remain in the upper layer and ) under two tillage systems (CT: conventional tillage, NT: No-tillage).…”
Section: Soil Tillagesupporting
confidence: 93%
“…These results are in agreement with Arshad et al (1995) who found that differences in weed infestation do not always result in significant yield differences. This lack of relation between weed biomass and crop yield could be explained by the occurrence of resources complementarity (no crop-weed competition).…”
Section: Soil Tillagesupporting
confidence: 93%
See 1 more Smart Citation
“…However, Arshad and Gill (1996) showed that NT increased field pea production as compared to CT in 2 of 3 yr. These workers also found, in another study, that yields of canola decreased in the order: reduced tillage > NT > CT (Arshad et al 1995). Lafond et al (1992) reported that NT resulted in higher yield of pea than CT, but gave comparable yields of winter wheat as CT in a heavy clay soil in Indian Head, Saskatchewan.…”
Section: Tillage Effectmentioning
confidence: 83%
“…Arshad et al, 1995;Blackshaw et al, 1994;Derpsch, 2003). Others, however, have found that reducing soil disturbance reduced weed populations.…”
Section: Laboratory Experimentsmentioning
confidence: 99%